Influence of leadership and loyalty on employee performance at royal regantris kuta during the covid-19 pandemic - Nyoman Surya Wijaya; Kadek Fricilya Aryantika; I Made Darsana (Institute of Computer Science (IOCS), 2023)
This is quantitative research conducted to examine the effect of leadership and loyalty on employee performance at Royal Regantris Kuta during the COVID-19 pandemic. The sample used was 32 people using the saturated sampling method consisting of all employees of the Royal Regantris Kuta. Data collected with likert scale questionnaire given to all samples, interviews and document recording. The data analysis technique used classicalassumption, coefficient of determination, multiple linear regression, T test and F test. The results are: (1) leadership variables had a significant positive effect on employee performance; (2) loyalty variable has a significant positive effect on employee performance; and (3) leadership and loyalty variables show simulant effect on employee performance.